Pelaksanaan Penanaman Nilai Pendidikan Karakter di SMA Bertalenta INS Kayu Tanam Kabupaten Padang Pariaman - Ripho Delzy Perkasa; Nuriza Dora; Cicilia Melinda (Universitas Batanghari Jambi, 2021)
This study aims to find out and analyze how the implementation of character education and the factors that influence the implementation of character education in SMA INS Kayu Tanam, Padang Pariaman Regency. This type of research is a qualitative research conducted at SMA INS Kayu Tanam with the research informants being the principal, the assembly of teachers and students or students. The data collection techniques used in this study were observation, interviews and documentation. The results of the research obtained in the field show that: 1) The implementation of character education at SMA INS Kayu Tanam can be said to be good by means of habituation carried out by students while in school and dormitory, 2) The factors that influence the implementation of character education at SMA INS Kayu Tanam can be divided into two groups, namely: a) There are those who are said to be supporting factors which include commitment and good cooperation from all parties in the school environment, both school residents who are within the school environment and parties outside the school such as the surrounding community in the school environment, b. There are what are said to be factors that hinder the implementation of character education in schools including unsupportive links, lack of school funds, lack of intense communication between the school and parents or guardians of students, lack of awareness of students who are rooted in comfort has not been able to adapt to the new environment and the lack of supervision from the school. In this case, the author suggests that the implementation of character education through habituation at SMA INS Kayu Tanam can be further improved so that the expected goals of the school by balancing brain abilities with morals can be realized.